Students Dimension of Wellness and Learning Engagement as Predictors on Motivation in Science - Santos, Flor Ann Zella V. Delos (International Journal of Research in Interdisciplinary Studies, 2025)
This study looks into the significance of students' dimensions of wellness and learning engagement as determinants of motivation in science. The study used a descriptive-correlational and predictive approach to determine the combined impact of these characteristics on students' motivation in science. The survey, conducted in integrated schools in the Cateel 2 District of the Philippines, had 100 respondents from Grades 9 and 10. The three-part survey examined students' well-being and learning engagement aspects as predictors of their willingness to learn science. Ethical considerations were strictly followed, including adherence to research ethics and gaining informed consent from both parents and students. The data collection process includes evaluating the study instrument, obtaining authorization from school authorities, and issuing informed consent forms. Data analysis included descriptive statistics, correlational analysis, and prediction approaches to determine the characteristics that influence student motivation in science. The findings demonstrated that students had high levels of wellness on emotional, spiritual, physical, social, and intellectual dimensions, as well as strong engagement in mental, emotional, and behavioral aspects of science study. A statistical analysis revealed a statistically significant positive relationship between the general wellness of students and their motivation in science, as well as a considerable positive relationship between students' learning engagement and their motivation in science. These findings have implications for educational stakeholders, indicating the need for targeted interventions to improve student motivation, engagement, and general well-being in science education.